Способи творення комерційних ергонімів= Ways of creating commercial ergonyms - Pidvalna, Viktoriya; Maslova, Yuliya; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Pidvalna Viktoriya, Maslova Yuliya, Zukow Walery. Способи творення комерційних ергонімів = Ways of creating commercial ergonyms. Journal of Education, Health and Sport. 2016;6(7):367-374. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57985 http://ojs.ukw.edu.pl/index.php/johs/article/view/3701 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 15.07.2016. СПОСОБИ ТВОРЕННЯ КОМЕРЦІЙНИХ ЕРГОНІМІВ WAYS OF CREATING COMMERCIAL ERGONYMS Підвальна Вікторія Pidvalna Viktoriya Маслова Юлія Maslova Yuliya Національний університет «Острозька академія» National University "Ostrog Academy" Zukow Walery Zukow Walery UMK w Toruniu UMK in Torun У статті проаналізовано чинники, що впливають на процес номінації комерційних ергонімів. Досліджено способи творення комерційних ергонімів. Ключові слова: ергонім, комерційне підприємство, спрямування, номінатор. Summary. The article analyzes the factors that influence the nomination process commercial ergonyms. Investigated ways of making commercial ergonyms. Key words: ergonyms, commercial enterprise orientation, nominating.